Evaluation of Clinical, Gram Stain, and Microbiological Cure Outcomes in Men Receiving Azithromycin for Acute Nongonococcal Urethritis: Discordant Cures Are Associated With Mycoplasma genitalium Infection. Issue 1 (January 2022) - Toh, Evelyn; Gao, Xiang; Williams, James A.; Batteiger, Teresa A.; Coss, Lisa A.; LaPradd, Michelle; Ren, Jie; Geisler, William M.; Xing, Yue; Dong, Qunfeng; Nelson, David E.; Jordan, Stephen J.
Abstract : Background: In men with nongonococcal urethritis (NGU), clinicians and patients rely on clinical cure to guide the need for additional testing/treatment and when to resume sex, respectively; however, discordant clinical and microbiological cure outcomes do occur. How accurately clinical cure reflects microbiological cure in specific sexually transmitted infections (STIs) is unclear. Methods: Men with NGU were tested for Neisseria gonorrhoeae, Chlamydia trachomatis (CT), Mycoplasma genitalium (MG), Trichomonas vaginalis, urethrotropic Neisseria meningitidis ST-11 clade strains, and Ureaplasma urealyticum (UU). Men received azithromycin 1 g and returned for a 1-month test-of-cure visit. In MG infections, we evaluated for the presence of macrolide resistance-mediating mutations (MRMs) and investigated alternate hypotheses for microbiological treatment failure using in situ shotgun metagenomic sequencing, phylogenetic analysis, multilocus sequence typing analyses, and quantitative PCR. Results: Of 280 men with NGU, 121 were included in this analysis. In the monoinfection group, 52 had CT, 16 had MG, 7 had UU, 10 had mixed infection, and 36 men had idiopathic NGU. Clinical cure rates were 85% for CT, 100% for UU, 50% for MG, and 67% for idiopathic NGU. Clinical cure accurately predicted microbiological cure for all STIs, except MG. Discordant results were significantly associated with MG-NGU and predominantly reflected microbiological failure in men with clinical cure. Mycoplasma genitalium MRMs, but not MG load or strain, were strongly associated with microbiological failure. Conclusions: In azithromycin-treated NGU, clinical cure predicts microbiological cure for all STIs, except MG. Nongonococcal urethritis management should include MG testing and confirmation of microbiological cure in azithromycin-treated MG-NGU when MRM testing is unavailable. Abstract : Resolution of nongonococcal urethritis signs and symptoms does not always correlate with microbiological cure; discordant cures occur in one-third of men. Clinical cure accurately correlates with Gram stain and microbiological cure for nongonococcal urethritis bacterial pathogens, except Mycoplasma genitalium .Supplemental digital content is available in the text.